Exequatur of foreign arbitral awards in Spain: commentary to the decision of the High Court of Justice of Murcia of 12th April 2019 - Castellanos Ruiz, María José (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
In decision of the High Court of Murcia of 12th April 2019, it is agreed the exequatur in Spain of an foreign arbitral award issued in Colombia, requested by the plaintiff Productos Florida, S.A. The grounds for refusal of the exequatur that are alleged by the defendant, AMC JUICES, S.L. and that are subject to analysis are: a) The award has not yet become binding on the parties, or has been set aside or suspended by a competent authority of the country in which, or under the law of which, that award was made. (art. V.1.e) New York Convention of 1958); b) Recognition or enforcement of the foreign arbitral awards would be contrary to its public policy (art. V.2.b) New York Convention of 1958). In short, the position of the Spanish courts in relation to The New York Convention of June 10, 1958 on the recognition and enforcement of foreign arbitral awards, is to favor the recognition and enforcement of foreign arbitral awards, so that only they reject the exequatur of an arbitral award for very clear and obvious reasons.